ARCTIC Identification of Pups and Yearling Wolves by Dentine Width in the Canine - The Pennsylvania State University CiteSeerX Archives (1985)
ABSTRACT. One hundred and thirty-nine wolf (Canis lupus) skulls and mandibles were collected from hunters and trappers of northern Quebec and Labrador during the winters of 1980-81 through 1983-84. The maximum width of the dentine-cementum wall in olf canine teeth was used to separate pups killed late in their first year h m yearlings killed early in their second winter of life. Both age classes may have a closed foramen at the apex of the root and a clear deposit of cementum with no opaque annulus. Key words: wolf (Canis lupus), canine teeth, dentine width, pups versus yearlings &SUh&. Au cours des hivers de 1980-81 B 1983-84,139 crânes et mandibules de loups (Canis lupus) furent recueillis chez des chasseurs et des piégeurs dans le nord du Quebec et au Labrador. L’epaisseur maximale de la paroi de la ntine et du cement des canines des loups servit de donnk aidant B séparer les louveteaux nés plus tard durant I’annke et vivant leur premiere annee, et les loups âgks d’un an tues durant le deuxibme hiver de leur vie. Les deux classes d’âge ont un orifice ferme au sommet de la racine dentaire et un dépôt transparent de cement sans anneau opaque. Mots cl&: loup (Canis lupus), canines, épaisseur de la dentine, louveteaux contre loups âgés d’un an Traduit pour le journal par Maurice Guibord.